Treating Posttraumatic Stress Disorder in Female Victims of Trafficking Using Narrative Exposure Therapy: A Retrospective Audit - Robjant, Katy; Roberts, Jackie; Katona, Cornelius (Frontiers in Psychiatry, 2017)
Background: Human trafficking is a form of modern slavery that involves the forced movement of people internally within countries, or externally across borders. Victims who are trafficked for sexual exploitation are subject to repeated, multiple trauma, and high rates of mental health problems including PTSD have been found. Methods: In this pilot study, we used Narrative Exposure Therapy to treat 10 women who had been trafficked for sexual exploitation who were diagnosed with PTSD. Results: All 10 women completed the therapy and experienced a reduction in PTSD severity scores at post treatment, with improvements that were maintained or further improved at three month follow-up. General distress was also significantly reduced following treatment. Conclusions: Although limited by sample size and design, this pilot study demonstrates that Narrative Exposure Therapy is a feasible treatment for PTSD in this population and warrants further evaluation in a randomized controlled trial. Further adjunctive interventions may also be necessary to treat the additional psychological problems experienced by this population.